Anti-immigration attitudes in different welfare states: Do types of labor market policies matter?. (April 2015) - Nagayoshi, Kikuko; Hjerm, Mikael
This research sheds light onto the effects of welfare policies on anti-immigration attitudes by focusing on qualitative differences in these policies over time. Previous studies provide little evidence that welfare policies affect levels of anti-immigration attitudes because they view the welfare state in an overly abstract manner in relation to attitudes toward immigration. From this viewpoint, this research focuses on differences in a specific aspect of welfare policies, i.e. labor market policies, according to level and type of activation. By analyzing cross-national data over time, we determine that labor market policies in the form of activation policies indeed affect attitudes toward immigration. We also show that the effects vary across different types of labor market policies and depend on individual levels of socioeconomic vulnerability. Thus, this article provides a first step to rethinking how we conceptualize the welfare state in relation to anti-immigrant attitudes.